2023
DOI: 10.7150/thno.85823
|View full text |Cite
|
Sign up to set email alerts
|

LncRNAs associated with oxidative stress in diabetic wound healing: Regulatory mechanisms and application prospects

Abstract: Diabetes is a group of chronic diseases with blood glucose imbalance, and long-term hyperglycaemia causes sustained damage to various organs of the body, resulting in vascular lesions, neuropathy and impaired wound healing. Diabetic wound formation involves a variety of complex mechanisms, and they are characterized by a persistent chronic inflammatory response, degradation of angiogenesis and imbalance of extracellular matrix regulation, all of which are related to oxidative stress. Additionally, repair and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 129 publications
0
6
0
Order By: Relevance
“…, with concentrations reaching 10 × 10 −6 to 1000 × 10 −6 M. 33,34 Studies have also indicated a close correlation between long noncoding ribonucleic acid (RNA) and the production of ROS in diabetes. 35 Excessive accumulation of ROS has been proven to induce damage to various cells (such as keratinocytes, fibroblasts, and endothelial cells), impair cell viability, and inhibit functions such as migration and differentiation. 36,37…”
Section: Challenges In Diabetic Wound Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…, with concentrations reaching 10 × 10 −6 to 1000 × 10 −6 M. 33,34 Studies have also indicated a close correlation between long noncoding ribonucleic acid (RNA) and the production of ROS in diabetes. 35 Excessive accumulation of ROS has been proven to induce damage to various cells (such as keratinocytes, fibroblasts, and endothelial cells), impair cell viability, and inhibit functions such as migration and differentiation. 36,37…”
Section: Challenges In Diabetic Wound Treatmentmentioning
confidence: 99%
“…31 The concentration of H 2 O 2 in plasma ranges from 1 Â 10 À6 to 8 Â 10 À6 M (average: 3 Â 10 À6 M), and the average concentration of ROS in healthy cells is 1 Â 10 À6 M. 32 However, in diabetic wounds, sustained high blood sugar can lead to excessive accumulation of ROS through various pathways, such as polyol, advanced glycation end-products (AGEs)/receptor for AGEs, hexosamine, protein kinase C, etc., with concentrations reaching 10 Â 10 À6 to 1000 Â 10 À6 M. 33,34 Studies have also indicated a close correlation between long noncoding ribonucleic acid (RNA) and the production of ROS in diabetes. 35 Excessive accumulation of ROS has been proven to induce damage to various cells (such as keratinocytes, fibroblasts, and endothelial cells), impair cell viability, and inhibit functions such as migration and differentiation. 36,37 2.2.3 Associated abnormal inflammation.…”
Section: Diabetes Affects Normal Wound Healingmentioning
confidence: 99%
“…Persistent hyperglycemic environment promotes the production of ROS, thereby promoting the inflammation cascade reaction and stimulating oxidative stress, thus forming a vicious circle and eventually leading to chronic wounds. 13 Inspired by the antioxidant activity of hydrogels in free-radical scavenging experiments, we further measured their intracellular antioxidant activity using the DCFH-DA probe. As shown in Figure 7f, the quantity and intensity of fluorescence dots significantly increased after LPS stimulation; however, the increment was reduced by the treatment of hydrogel extracts.…”
Section: Water Content and Swellingmentioning
confidence: 99%
“…Persistent infection and excessive reactive oxygen species (ROS) resulting from hyperglycemia can exacerbate inflammatory reactions, leading to oxidative damage and impaired immune cell function, ultimately hindering wound healing. , Berberine (BER) is an isoquinoline alkaloid and exhibits a range of pharmacological activities, including antibacterial, anti-inflammatory, antioxidant, and regulation of glucose and lipid metabolism . These properties make it a promising candidate for alleviating inflammation and oxidative stress in DU.…”
Section: Introductionmentioning
confidence: 99%
“… 42 LncRNAs have regulatory functions in cell proliferation, invasion, metastasis, apoptosis, and immune response, which are accomplished through epigenetic modification, transcriptional regulation, and translational regulation. 43 LncRNAs are inextricably linked to the regulation of cellular functions and critical biological pathways, demonstrating their potential in diabetic wound healing. The overexpression of linc00511 in ADSC-exos demonstrated competency in DFU healing through inducing angiogenesis, which was attributed to suppressing PAQR3-induced Twist1 ubiquitination degradation.…”
Section: The Mechanism Of Stem Cell-evs In Diabetic Wound Healingmentioning
confidence: 99%